About old coins that are found in the area of the Upper Noteć Basin - Zakrzewski, Zygmunt (Acta Archaeologica Lodziensia, 2023)
The article deals with finds of Greek, Celtic, Roman and early medieval coins found in the area of the upper Noteć basin (part of Kuyavia, Pałuki, Krajna) and their interpretation. The author points out that the numismatic finds from this area constitute a clear concentration throughout Poland